Shear behaviors of recycled aggregate sand in constant volume simple shear tests interrelated with particle shape - Chen, Guanyu; Wu, Dazhi; Wang, Zhe; Liu, Shu; Zhou, Pan; Hu, Juntao (Frontiers in Earth Science, 2023)
Compared with quartz sand, recycled aggregate sand is characterized by its high liquefaction and shear resistance because of the irregular particle shape. However, the interrelationship between the particle shape and structure shear behaviors is seldom investigated. By conducting a number of monotonic and cyclic simple shear tests under undrained constant volume situations, this paper investigates the role of particle shape on the shear behaviors of recycled aggregate sand. The particles’ morphology parameters were assessed in terms of sphericity, roundness and regularity through microscopic observation and image processing. According to the experimental results, the recycled aggregate sand with irregular shapes mobilize greater gradients of the flow liquefaction lines under monotonic shearing conditions. The irregular particles also lead to greater peak shear stress and dynamic shear modulus, indicating stronger shear and liquefaction resistances under cyclic shearing. Furthermore, the interrelationships between the peak shear stress, dynamic shear modulus and particle shape of the samples are found and established by well fitted functions as references for the selection of recycled aggregate sand and corresponding designs of the foundation engineering.